The Status of Adat Law in Traditional Courts: Between Validity and Legitimacy in the Eyes of National Law - Rosalia, Olyvia; Nurahman, Dwi (Journal of Adat Recht, 2025)
This study examines the position of customary law within Indonesia’s customary courts, exploring the delicate balance between legality and legitimacy from the perspective of national law. Customary law holds a significant place in Indonesia’s pluralistic legal system, recognised constitutionally and through various statutes such as Law Number 6 of 2014 on Villages and Law Number 48 of 2009 on Judicial Power. However, its practical enforcement and integration remain challenged by legal ambiguities and limited formal recognition, particularly concerning customary courts’ jurisdiction and authority. This research employs a normative legal approach, analysing relevant legislation, constitutional provisions, and judicial decisions to understand how customary law navigates between formal legality and the social legitimacy derived from indigenous communities. The findings reveal that while customary law is socially and culturally legitimate within indigenous societies, it often occupies a marginalised position within the state legal framework. Customary courts play a crucial role in mediating disputes and preserving indigenous identity, yet face constraints due to their limited legal empowerment. The study also highlights the need for comprehensive legal reforms and policies that enhance customary law’s status, promote cooperation between customary and state legal systems, and respect cultural diversity. Comparative insights from other pluralistic jurisdictions further underscore the potential for harmonising customary and national law to achieve justice and social cohesion in Indonesia.